Effectiveness Use of Working Capital During The Covid-19 Pandemic at PT. Mitra Adiperkasa Tbk. - Muhammad Astri Yulidar Abbas; Larasati Larasati (Jurnal Mantik, 2022)
The purpose of this study is to determine and analyze whether the use of working capital is effective at PT Mitra Adiperkasa Tbk and similar companies as a comparison listed on the Indonesia Stock Exchange. This research method is descriptive research with a quantitative approach, namely by collecting, processing, simplifying, presenting, and analyzing financial report dataat PT Mitra Adiperkasa Tbk in 2020. The variables used in this study are accounts receivable turnover, inventory turnover, and working capital turnover.Based on the results of the analysis and discussion, it can be said that trade receivables turnover in 2020 is below the industry average, and inventory turnover and working capital turnover in 2020 are below the industry average so that it can be stated that the use of working capital at PT Mitra Adiperkasa Tbk is not effective.